Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3200/jmbr.39.5.369-380
|View full text |Cite
|
Sign up to set email alerts
|

Perception-Action Coupling and Anticipatory Performance in Baseball Batting

Abstract: The authors examined 10 expert and 10 novice baseball batters' ability to distinguish between a fastball and a change-up in a virtual environment. They used 2 different response modes: (a) an uncoupled response in which the batters verbally predicted the type of pitch and (b) a coupled response in which the batters swung a baseball bat to try and hit the virtual ball. The authors manipulated visual information from the pitcher and ball in 6 visual conditions. The batters were more accurate in predicting the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 21 publications
(31 reference statements)
9
100
1
4
Order By: Relevance
“…This supports the results reported by Mann et al (in press), giving weight to the case for a coupling-facilitated improvement in performance, since the task more closely replicates the real-world conditions (Farrow & Abernethy, 2003). This is in contrast to the alternate view that stronger coupling may result in decreased performance as a result of increased task complexity or of requiring participants to make an earlier response (Ranganathan & Carlton, 2007). Most interestingly, the support for coupling-enhanced anticipation in the absence of confirmatory ball-flight information supports the role of movement in facilitating anticipation, and is consistent with the van der Kamp et al (2008) model, according to which the dorsal visual stream makes critical contributions to anticipation even when decisions are based purely on pre-ball-flight information.…”
Section: Visual Blur and Perception-action Couplingsupporting
confidence: 89%
“…This supports the results reported by Mann et al (in press), giving weight to the case for a coupling-facilitated improvement in performance, since the task more closely replicates the real-world conditions (Farrow & Abernethy, 2003). This is in contrast to the alternate view that stronger coupling may result in decreased performance as a result of increased task complexity or of requiring participants to make an earlier response (Ranganathan & Carlton, 2007). Most interestingly, the support for coupling-enhanced anticipation in the absence of confirmatory ball-flight information supports the role of movement in facilitating anticipation, and is consistent with the van der Kamp et al (2008) model, according to which the dorsal visual stream makes critical contributions to anticipation even when decisions are based purely on pre-ball-flight information.…”
Section: Visual Blur and Perception-action Couplingsupporting
confidence: 89%
“…Thus, this cognitive judgement regarding the pitcher's motion would be made in an unconscious manner and contribute to any adjustment of the swing timing. Many studies have suggested the importance to batting information about the pitcher's motion [6,7]. Our result directly supports this suggestion using virtual space.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas Experiment 2 was conceptualized so as to address further methodological concerns besides investigating expert-novice differences within the IB paradigm, Experiment 3 was designed to strengthen the practical implications of the findings by strengthening ecological validity. In Experiment 3, we investigated whether actually carrying out the tactical decision via a motor response and, thus, creating a more dynamic and sport-related situation would influence the occurrence of IB, since the poor perception-action coupling in Experiments 1 and 2 might have influenced the result pattern (Ranganathan & Carlton, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…To strengthen the finding of Experiments 1 and 2, it is essential to further improve the ecological validity of the real-world basketball task. A major limitation of a large body of research in sport psychology is that perception-action coupling is poor when participants have to respond to visual stimuli by using verbal, written, or buttonpressing responses instead of actual motor responses (Ranganathan & Carlton, 2007). For this reason, laboratorybased testing procedures requiring non-sport-specific responses, such as pressing a button or naming the tactical decision, as utilized in the studies of Memmert and Furley (2007), have their limitations for studying attention in the field of sport.…”
Section: Methodsmentioning
confidence: 99%